Turismo como criador de mercado para o artesanato em Mato Grosso do Sul - Violin, Fábio Luciano [UNESP] (Universidade Católica Dom Bosco, 2022)
The object of the study was tourism as an instrument of market production for handicrafts from Mato Grosso do Sul. The objective of the research was to analyze the relationship between tourist activity and handicraft in the state, and, for this purpose, semi-structured interviews were carried out with those responsible for handicraft stores, tourists, and autochthonous people along all the entrances in the state of Mato Grosso do Sul and its rising and falling tourist destinations, thus covering the entirety of supply points and localities of incidence of production and consumption of handicraft items. This action resulted in on-site observations and the generation of photographic records illustrating the points susceptible of inference. The results show an inseparable relationship between tourism and handicraft, since the first produces a market for the second, which in turn molds itself to the first, with a relationship engendered from the demand of tourists who use the active tourist circuit. However, the tripod of sustainable development – economy, environment, and society – is not a reference for companies that sell handcrafted items to tourists, which are limited to seeing commerce as an exclusive source of profit, with few representatives genuinely interested in the context of culture and of the story that a handcrafted piece can represent.

El objeto del estudio fue el turismo como instrumento de producción de mercado de artesanías de Mato Grosso do Sul. El objetivo de la investigación fue analizar la relación entre la actividad turística y la artesanía en el estado y por lo tanto, se realizaron entrevistas semiestructuradas con los responsables de tiendas de artesanías, turistas y autóctonos a lo largo de todos los accesos del estado de Mato Grosso do Sul y sus destinos turísticos en alza y caída, cubriendo, así, la totalidad de los puntos de abastecimiento y localidades de incidencia de la producción y consumo de artículos artesanales. Como resultado de esta acción, resultaron las observaciones in loco y la generación de registros fotográficos ilustrativos de los puntos susceptibles de inferencia. Los resultados muestran una relación inseparable entre turismo y artesanía, ya que el primero produce un mercado para el segundo, que, a su vez, se amolda al primero, con una relación engendrada a partir de la demanda de turistas que utilizan el circuito turístico activo. Sin embargo, el trípode del desarrollo sostenible – economía, medio ambiente y sociedad – no es un referente para las empresas que venden artículos artesanales a los turistas, que se limitan a ver el comercio como una fuente exclusiva de lucro, con pocos representantes genuinamente interesados en el contexto de la cultura y de la historia que una pieza artesanal puede representar.

O estudo teve como objeto o turismo enquanto instrumento de produção de mercado para o artesanato sul-mato-grossense. O objetivo da pesquisa visou analisar a relação entre a atividade turística e o artesanato no estado e, para tanto, foram realizadas entrevistas semiestruturadas com responsáveis por lojas de artesanato, turistas e autóctones ao longo de todas as entradas do estado de Mato Grosso do Sul e seus pontos turísticos em ascensão e em queda, cobrindo, dessa forma, a totalidade de pontos de oferta e localidades de incidência de produção e consumo de peças artesanais. Decorreram dessa ação as observações in loco e a geração de registros fotográficos ilustrativos dos pontos passíveis de inferência. Os resultados evidenciam relação indissociável entre o turismo e o artesanato, uma vez que o primeiro produz mercado para o segundo, que, por seu turno, molda-se ao primeiro, existindo uma relação engendrada a partir da demanda dos turistas que se valem do circuito turístico ativo. Contudo, o tripé do desenvolvimento sustentável – economia, ambiente e sociedade – não é referência para as empresas que vendem peças artesanais aos turistas, que se resumem a ver o comércio como fonte exclusiva de lucro, existindo poucos representantes genuinamente interessados no contexto da cultura e da história que uma peça artesanal pode representar.
Tourism as a market creator for handicrafts in Mato Grosso do Sul
El turismo como creador del mercado de artesanías en Mato Grosso do Sul
Keywords: regional development; environment; craft trade; desenvolvimento regional; meio ambiente; comércio de artesanato